Book Review: Place, Being, Resonance: A Critical Ecohermeneutic Approach to Education - Leggo, Carl (Journal of the Canadian Association for Curriculum Studies, 2018)
As a poet, I am always seeking to live poetically, informed and motivated by the rhythms and wisdom of poetry. Michael W. Derby’s Place, Being, Resonance: A critical Ecohermeneutic Approach to Education is a poetic rumination on place and ecological living. With attention to the etymology of ecopoiesis, Michael is making a home for dwelling, and he is calling others to engage in this home-making, where we do not take for granted the cultural norms and processes. Michael understands the efficacy of education for transformation. He understands the mystery of the ineffable, but he also understands the urgency to acknowledge how the ineffable is always dancing a wild tango with the effable. The role of education is to keep the mind, heart, spirit, intuition and imagination supple and nimble, always attuned to other possibilities.